Актуальність регулювання правил виключення в системі кримінального правосуддя Індонезії (ПРАВОВІ ГОРИЗОНТИ, 2024)
This study addresses the legal gap related to the application of the principle of exceptional rules of evidence in Indonesia. Currently, there is no clear provision prohibiting the use of evidence obtained through illegal means, such as torture, threats, or pressure on suspects. This practice is often used by law enforcement officers to obtain confessions from suspects and bring the case to trial. Without a clear legal mechanism, illegal evidence is often used, which not only harms the rights of suspects, but also undermines the principles of justice, weakens legal protection, and damages the image of the judiciary in the eyes of society. This legal vacuum leads to the fact that human rights violations continue to occur without strict sanctions against the perpetrators. This study uses a normative and legal method using legislative, conceptual, precedential, and comparative approaches. The analysis is carried out through a systematic and grammatical interpretation of primary, secondary, and tertiary legal materials. The results show the urgency of regulating the principle of exclusionary rules in the KUHAP to ensure that only legally obtained evidence is used in court. As a normative model, Indonesia can adopt the provisions of Article 359a paragraph (1) letter b of the Dutch Wetboek van Strafvordering (WvSv), which provides a clear mechanism for excluding illegal evidence. The implementation of this principle will strengthen the protection of human rights, ensure a fair trial, and increase the responsibility and professionalism of law enforcement officers in the performance of their duties.